Anti-CRT Attacks, School Choice, and the Privatization Endgame - Maharaj, Sachin; Tuters, Stephanie; Shah, Vidya (Critical Education, 2024)
Across Canada, school districts have been confronting a backlash to their equity and social justice initiatives. Critics of public education have been arguing that the solution to these controversies is to increase school choice. Using several examples from the United States, this paper argues that the endgame of these strategies is to undermine the legitimacy of public education and increase support for private alternatives. To protect its future viability, the paper also calls on public education advocates to grapple with ongoing marginalization within school systems which make private options increasingly attractive.